Gallstones in liver transplant recipients: A single-center study in China - Shi, Rui; Shen, Zhong-Yang; Teng, Da-Hong; Zheng, Wei-Ping; Zhu, Zhi-Jun; Deng, Yong-Lin; Pan, Cheng; Tian, Zhongping; Zheng, Hong (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Liver transplant recipients include patients who present with almost all kinds of end-stage liver disease. Studying the relationship between gallstones and end-stage liver disease among liver transplant recipients is becoming important. Materials and Methods: Multiple logistic regression analysis was applied to assess 1640 liver transplant recipients. Multiple factors were involved in the analysis, including age, sex, total bilirubin and total cholesterol levels, Child score, hepatitis B virus (HBV) infection, hepatitis C virus (HCV) infection, alcoholic cirrhosis, and hepatocellular carcinoma (HCC). Results: Age and Child score are independent risk factors for the development of gallstone disease (GD). The average age of the recipients in the GD group was 49.22±9.96 years, which was significantly higher than that in the GD-free group (48.23±9.79 years). The Child score of the recipients in the GD group was 9.21±2.47, which was significantly lower than that of the recipients in the GD-free group, which was 8.79±2.48 (t=3.23, p<0.001). We also found that hepatitis B is an influential factor in GD. Conclusion: The prevalence of gallstones among liver transplant recipients is related to the Child score and patient age. The prevalence of GD is lower in patients with HCC and in those who are HBV positive and is relatively higher in HCV-positive patients and in those with alcoholic cirrhosis, although no significant differences were found.